The Impact of Real Exchange Rate Volatility on Foreign Direct Investment Inflows in Tunisia - Hniya, Sakli; Boubker, Ahlem; Mrad, Fatma; Nafti, Sawssen (International Journal of Economics and Financial Issues, 2021)
This article aims to determine the impact of the Real Effective Exchange Rate (REER) and its volatility on Tunisian Foreign Direct Investment (FDI) Inflows for the period from 1980 to 2018. By applying the Auto Regressive Distributed Lag (ARDL) model, we noticed that an increase in exchange rate volatility tends to lower FDI inflows over a long-term horizon. We have also shown that an increase in REER, equivalent to a real appreciation (quotation at certain), will decrease FDI. While in the short term, the relationship between REER and FDI is positive, while volatility retains its negative long term effect. Keywords: Foreign Direct Investment, Real Effective Exchange Rate Volatility, ARDL Model, Tunisia JEL Classifications: C130, G150, F310 DOI: https://doi.org/10.32479/ijefi.11882